(3eONd Edi Yde GdELJeGY (B/ s - (3HdYdej, cdJhes; (3LGeYI GdLRGFQ(B3: (3cdjI GdYdhe GdEbJUGOjI, GdYdhe GdJLGQjI hYdhe GdJSjjQs ((3GdLRGFQs (3LGeYI GdLRGFQ(B3: (3cdjI GdYdhe GdEbJUGOjI, GdYdhe GdJLGQjI hYdhe GdJSjjQs, 2017)
(3GdJYQja HYde GdELJeGY, XQha fTCI Yde GdELJeGY, GdJYQja HYde GdELJeGY GdEbJUGOj, GdJZjQ GdELJeGYj hGdEgJeGeGJ GdcHQi dYde GdELJeGY, GdfXQjI hGdefGgL aj Yde GdELJeGY, YHO GdQMeGf GHf NdOhf, GhZjSJ chfJ, Gejd OhQcGje, cGQd eGcS, eGcS ajHQ, GdfXQjI GdHfGFjI GdhXjajI, GdfXQjI GdJaGYdjI GdQeRjI, GdJMdjd GdGSJQGJjLj, eaGgje CSGSjI aj Yde GdELJeGYs
(3HHdjhZQGajG(B: (3U(B.77s
Keywords: (3GdGLJeGY GdGbJUGOj, Ydes; (3GdGLJeGY, Ydes; (3GdYdhe GdGLJeGYjIs